Análise numérica do processo de mudança de fase com PCM em tubos elípticos de trocadores de calor - Vieira, Matheus (Universidade do Vale do Rio dos Sinos, 2021)
As Phase Change Materials (PCM) have a high energy storage capacity in relation to their volume, they have a high potential for use in mechanisms to improve energy efficiency. Their thermal energy storage occurs through latent heat during the phase change process. Therefore, they can be widely used in heat exchangers, since the thermal exchange that occurs in this process allows the solidification and/or fusion process of materials depending on their temperature. In this essay, a numerical study of the fusion process of the PCM RT - 82 contained in an elliptical multiple tube heat exchanger is performed. This condition is analyzed by varying the geometric conditions of the tubes, the vertical eccentricity of the tubes in relation to the PCM rings and their orientation. The analysis is conducted by using CFD (Computational Fluid Dynamics) on the FLUENT software. The problem presented is two-dimensional, vertically symmetric and transient. The mathematical model is composed of the equations for the conservation of mass, energy and momentum. The numerical model is validated with experimental and numerical results from the literature. The results for total melting time, liquid fraction as well as liquid fraction and velocity fields are presented. The results show that among the geometric variations carried out in the study, the factor that most influences the reduction of the total melting time of the PCM is the tube eccentricity.
Keywords: Materiais de mudança de fase (PCM); Armazenamento de energia; Fusão; Fluidodinâmica computacional; Phase Change Materials (PCM); Energy storage; Fusion.; Computational Fluid Dynamics